Prostate Cancer and DNA Genes Repair: What Should an Oncologist Know? – A Narrative Review - Santos de Azevedo, Fernando; Morais de Santana Sá, Lanúscia; Maíra de Resende, Uirá; Ribeiro Gabriel, Augusto; de Paula Silveira Lacerda, Elisângela (HM Publisher, 2023)
Prostate cancer is a very prevalent disease in men, especially in Western countries. The treatment of this neoplasm, both localized and locally advanced, is based on the clinical risk analysis (Gleason, tumor size, PSA, and other factors) and is founded on surgery and/or radiotherapy with or without androgen blockade with a GnRH analog (hormone gonadotropin releaser). However, in patients who invariably progress to a metastatic disease scenario, the tumors may present a heterogeneous behavior, depending on whether or not they are sensitive to androgen blockade therapy. Due to the poor prognosis of the metastatic castration-resistant scenario, current research carried out in the molecular biology and genetics field has identified several gene alterations associated with the development of prostate cancer, which correlate with clinical risk, therapeutic predictive responses, and prognosis. Among the associated gene alterations, the genes of the DNA repair pathway are correlated with diseases that present: a higher risk of recurrence; early metastasis; worse cancer-specific survival; familial risk, and predictive responses to new targeted therapies. Therefore, the breast cancer susceptibility genes, BRCA1 and BRCA2 (and other variants), present in the DNA repair machinery are being investigated to provide more (and better) therapeutic options for the treatment of the disease in the advanced scenario. This review was aimed to describe the malignant prostate disease, especially with regard to DNA repair mechanisms, genomic analysis of prostate cancer, predictive and prognostic implications, as well as on the development of poly-(ADP-ribose) polymerase (PARP) inhibitors, synthetic lethality mechanisms, and BRCAness phenomenon.